AL2O3 - CL / PD CATALYSTS SYNTHESIS TO DO - I.A. Anvarova,; D.Sh.Shukurova, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Abstract: Current on the day in the world catalysts synthesis to do and synthesis made catalysts based on new products to take main current from problems one is considered. This at work aluminum palladium catalyst synthesis to do for necessary reagents working issued and taken catalyst composition, physicochemical properties brought passed.